Validation of SNP markers for diversity analysis, quality control, and trait selection in a biofortified cassava population - Mbanjo, Edwige Gaby Nkouaya; Ogungbesan, Adebukola; Agbona, Afolabi; Akpotuzor, Patrick; Toyinbo, Seyi; Iluebbey, Peter; Rabbi, Ismail Yusuf; Peteti, Prasad; Wages, Sharon A.; Norton, Joanna; Zhang, Xiaofei; Bohorquez-Chaux, Adriana; et al. (MDPI, 2024)
A validated marker system is crucial to running an effective genomics-assisted breeding program. We used 36 Kompetitive Allele-Specific PCR (KASP) markers to genotype 376 clones from the biofortified cassava pipeline, and fingerprinted 93 of these clones with DArTseq markers to characterize breeding materials and evaluate their relationships. The discriminating ability of the 36-quality control (QC) KASP and 6602 DArTseq markers was assessed using 92 clones genotyped in both assays. In addition, trait-specific markers were used to determine the presence or absence of target genomic regions. Hierarchical clustering identified two major groups, and the clusters were consistent with the breeding program origins. There was moderate genetic differentiation and a low degree of variation between the identified groups. The general structure of the population was similar using both assays. Nevertheless, KASP markers had poor resolution when it came to differentiating the genotypes by seed sources and overestimated the prevalence of duplicates. The trait-linked markers did not achieve optimal performance as all markers displayed variable levels of false positive and/or false negative. These findings represent the initial step in the application of genomics-assisted breeding for the biofortified cassava pipeline, and will guide the use of genomic selection in the future.